2015
DOI: 10.1016/j.jpowsour.2015.01.054
|View full text |Cite
|
Sign up to set email alerts
|

Triple phase boundary specific pathway analysis for quantitative characterization of solid oxide cell electrode microstructure

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 21 publications
0
63
0
Order By: Relevance
“…Previous 3D-reconstructions of similar Ni-stabilized zirconia electrodes have shown that electrodes having same phase fractions, similar PSDs and even comparable percolating TPB densities can have significantly different critical pathway radii for the Ni network, tortuosity for the percolating Ni path and significant differences in the number of percolating paths from the electrode/electrolyte interface to the outer circuit. These parameters were shown to affect the electrochemical performance significantly [22]. Based on those results and the observation of the microstructural changes in Cell D we therefore hypothesize that also the necking between Ni-Ni particles and the Ni-YSZ…”
Section: Select Test Conditions Based On Electrode Overpotentialmentioning
confidence: 56%
See 1 more Smart Citation
“…Previous 3D-reconstructions of similar Ni-stabilized zirconia electrodes have shown that electrodes having same phase fractions, similar PSDs and even comparable percolating TPB densities can have significantly different critical pathway radii for the Ni network, tortuosity for the percolating Ni path and significant differences in the number of percolating paths from the electrode/electrolyte interface to the outer circuit. These parameters were shown to affect the electrochemical performance significantly [22]. Based on those results and the observation of the microstructural changes in Cell D we therefore hypothesize that also the necking between Ni-Ni particles and the Ni-YSZ…”
Section: Select Test Conditions Based On Electrode Overpotentialmentioning
confidence: 56%
“…This reduction procedure was chosen to make the NiO reduction procedure similar to several previously reported SOEC test (e.g. [7,10,12] ) and kept constant as previously reported results of 3D reconstructions of fuel electrodes show that the reduction profile can affect the fuel electrode microstructure significantly [22]. Hereafter performance characterization via iV-curves and electrochemical impedance spectroscopy (EIS) was conducted.…”
Section: Test Procedures and Operating Conditionsmentioning
confidence: 99%
“…4) The fast marching method calculates the shortest path through the analysed phase by creating a distance map between the starting and end boundary of a propagating front. The shortest path between the two boundaries of the sample is then read out of the distance map and divided by the Euclidean distance of the starting and end boundary to calculate the geometric tortuosity (Jørgensen et al, 2011;Jørgensen et al, 2015;Taiwo et al, 2016a).…”
Section: Image-based Tortuosity Calculation Approachesmentioning
confidence: 99%
“…High electrochemical performance required a high TPB in the anode, because increasing the TPB density will enhance the kinetics of the oxidation reaction that occurs between oxygen ions and methane fuel on the anode side of the cell, and thus increase cell performance. Using 3D imaging techniques like FIB-SEM [14,[30][31][32][33], the nanocomposite anodes with optimized electrode microstructure exhibit substantially higher TPB density, leading to higher cell performance and better stability [15,16,[34][35][36]. Therefore, the new double-pore NiO-SDC anode with a wider TPB area is much more promising for direct-methane solid oxide fuel cells, compared with the conventional single-pore NiO-SDC anode.…”
Section: Electrochemical Performance Of Single Cellsmentioning
confidence: 99%
“…Recently, some new microstructure for NiO-SDC anodes were investigated as alternative anode materials for direct use with methane fuels, such as surface modification of NiO-SDC anode by impregnation [9][10][11]. This results have indicated that the adjustment of NiO-SDC anodes are very effective in suppressing catalytic carbon formation by blocking methane from approaching the nickel, which is catalytically active towards methane pyrolysis [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%